2021
DOI: 10.1021/acs.jproteome.1c00504
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Metabolomics Reveals that Metabolic Alterations Precede the Onset of Schizophrenia

Abstract: Schizophrenia is a complex and highly heterogeneous mental illness with a prodromal period called clinical high risk (CHR) for psychosis before onset. Metabolomics is greatly promising in analyzing the pathology of complex diseases and exploring diagnostic biomarkers. Therefore, we conducted salivary metabolomics analysis in 83 first-episode schizophrenia (FES) patients, 42 CHR individuals, and 78 healthy controls with ultrahigh-performance liquid chromatography-quadrupole time-of-flight mass spectrometry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…In this study, the other important pathway, Citrate cycle (TCA cycle) was found promoted in SCZ and associated with cognitive impairment in SCZ, which support the possibility that abnormalities in energy metabolism contribute to SCZ ( 32 ). To be specific, the hypothesis holds that TCA cycle affects inflammatory response and induces blood-brain barrier damage, which lead to the occurrence and development of SCZ and the core symptoms ( 33 35 ). Indeed, it has been found that the TCA cycle was abnormal in SCZ compared with HC, which is consistent with our results ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the other important pathway, Citrate cycle (TCA cycle) was found promoted in SCZ and associated with cognitive impairment in SCZ, which support the possibility that abnormalities in energy metabolism contribute to SCZ ( 32 ). To be specific, the hypothesis holds that TCA cycle affects inflammatory response and induces blood-brain barrier damage, which lead to the occurrence and development of SCZ and the core symptoms ( 33 35 ). Indeed, it has been found that the TCA cycle was abnormal in SCZ compared with HC, which is consistent with our results ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…To be specific, the hypothesis holds that TCA cycle affects inflammatory response and induces blood-brain barrier damage, which lead to the occurrence and development of SCZ and the core symptoms ( 33 35 ). Indeed, it has been found that the TCA cycle was abnormal in SCZ compared with HC, which is consistent with our results ( 33 ). While the correlation between TCA cycle and the cognitive level of SCZ still requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Oral metabolism disorders often precede the actual onset of schizophrenia, increase with the development of the disease and even could be its causative factor. Cui et al stressed that certain salivary microbiota exhibited disease-specific correlation patterns with symptomatic severities [117]. It might be explained by the production of pro-inflammatory cytokines and local immunological imbalance, amino acid metabolism, carbohydrate metabolism and xenobiotic degradation.…”
Section: The Relationship Of Thyroid Hormones With the Intensificatio...mentioning
confidence: 99%
“…The bodily functions, metabolic processes, hormonal changes, and emotional state are all reflected in the saliva. (5) A vast variety of the micro-organisms, several of which are the natural and beneficial supporting oral homeostasis, "peacefully" coexist in the oral cavity. Oral bacteria are impacted directly and indirectly by saliva and its numerous elements.…”
Section: Introductionmentioning
confidence: 99%